The Influence of a Foreign Versus Native Language on Creativity. Issue 4 (2nd October 2017) - Stephan, Elena
Abstract : Creativity may be enhanced by contextual factors that contribute to a divergence from conventional and habitual modes of thought. Two studies tested the prediction that a foreign language (that is frequently associated with moving away from the routine experiences) will contribute to originality of solutions, compared to one's native language. Findings demonstrate that a foreign language confers benefits for creativity on well-established nonverbal tasks . Participants were more creative in designing t-shirt outlines (Study 1) and in drawing an alien character for a story (Study 2) within the context of their foreign, as compared to the native, language. The potential underlying mechanisms and implications of the effect are discussed.